SPATIAL AND TEMPORAL VARIATION OF THE TOTAL SUSPENDED SOLID IN THE SOUTH SULAWESI COASTAL WATERS - Waode Rustiah; Alfian Noor; Maming Gaffar; Muhammad Lukman (Hasanuddin University, 2018)
Suspended solids are the main ingredients forming precipitates that can inhibit the ability to form organic compounds in coastal and marine waters. This study aims to determine the concentration of Total Suspended Solid (TSS) in coastal and marine waters of the west coast of South Sulawesi collected in different seasons, namely October 2017 (dry season) and March 2018 (rainy season). TSS concentrations generally higher in the rainy season (34-47 ppm) compared to the dry season (10-25 ppm). On location, higher TSS concentrations were obtained in the Tallo river waters, namely 10–47 ppm (28.9 ± 13.4 ppm) compared to locations in Pangkep river waters 14–43 ppm (27.4 ± 11.2 ppm). The results showed that the Total Suspended Solid (TSS) in marine waters and still comply with the limit values set by the Ministry of Environment (MOE).